Application of Mina Padi in Lidah Tanah Village, Perbaungan District, Serdang Bedagai Regency - Mayly, Syarifa (Journal of Saintech Transfer, 2020)
"Berkat" Farmers Group and "Serasi" Farmers Group are farmer groups located in Lidah Tanah Village, Perbaungan District. There are various problems found in the two farmer groups, which are: (a) Low / limited farmer income, (b) Increasing pests and diseases attack, (c) Unfamiliarity about mina padi lele cultivation system and do not implement it to increase their income, to optimize land, to reduce pest and weed attacks, to increase the efficiency of fertilizers and water usage, (d) Farmers do not know and do not implement routine pest monitoring systems, (e) Farmers have no knowledge about organic pesticides production, (f) Farmers have no knowledge about organic feed production for catfish cultivation and (g) Environmental pollution due to excessive use of pesticides and less utilization of harvest waste such as rice straw. The solution to overcome these various problems is by applying mina padi lele technology, which is a farming system by combining the techniques of rice cultivation and raising fish simultaneously in paddy fields. The results showed that the application of the mina padi lele cultivation system greatly benefited farmers, where organic rice produced from the mina padi lele system was 263.5 kg/rante (1 rante equals to 625 m2) with additional 57.5 kg/rante of organic catfish products while non-organic rice produced from cultivation conventionally applied by farmers is 257.6 kg / rante.